Epidemiological and Molecular Analysis of an Outbreak of Highly Pathogenic Avian Influenza H5N8 clade 2.3.4.4 in a German Zoo: Effective Disease Control with Minimal Culling. Issue 6 (15th November 2016) - Globig, A.; Starick, E.; Homeier, T.; Pohlmann, A.; Grund, C.; Wolf, P.; Zimmermann, A.; Wolf, C.; Heim, D.; Schlößer, H.; Zander, S.; Beer, M.; et al.
Summary: Outbreaks of highly pathogenic avian influenza A virus (HPAIV) subtype H5N8, clade 2.3.4.4, were first reported in January 2014 from South Korea. These viruses spread rapidly to Europe and the North American continent during autumn 2014 and caused, in Germany, five outbreaks in poultry holdings until February 2015. In addition, birds kept in a zoo in north‐eastern Germany were affected. Only a few individual white storks ( Ciconia ciconia ) showed clinical symptoms and eventually died in the course of the infection, although subsequent in‐depth diagnostic investigations showed that other birds kept in the same compound of the white storks were acutely positive for or had undergone asymptomatic infection with HPAIV H5N8. An exception from culling all of the 500 remaining zoo birds was granted by the competent authority. Restriction measures included grouping the zoo birds into eight epidemiological units in which 60 birds of each unit tested repeatedly negative for H5N8. Epidemiological and phylogenetical investigations revealed that the most likely source of introduction was direct or indirect contact with infected wild birds as the white storks had access to a small pond frequented by wild mallards and other aquatic wild birds during a period of 10 days in December 2014. Median network analysis showed that the zoo bird viruses segregated into a distinct cluster of clade 2.3.4.4 with closest ties to H5N8 isolates obtained from mute swans ( Cygnus olor ) in Sweden in April 2015. This case demonstrates that alternatives to culling exist to rescue valuable avifaunistic collections after incursions of HPAIV.